Severe Anemia Normocytic Normochromic EC CKD (Oshada, 2025)
This study aims to clinically describe a case of severe normocytic normochromic anemia due to chronic kidney disease (CKD) and contribute to strengthening medical understanding of the relationship between anemia and kidney dysfunction. The method used is a descriptive case study with a clinical observation approach and literature review. Data were obtained from a 58-year-old male patient who came to the Emergency Department of M. Natsir Solok Regional Hospital complaining of weakness, pallor, joint pain, and decreased appetite. Laboratory examination results showed a hemoglobin level of 5.8 g/dL and creatinine of 8.13 mg/dL, indicating severe anemia due to stage V CKD. The patient underwent PRC transfusion therapy, intravenous fluids, and folate and antihypertensive administration. During four days of treatment, the patient's condition showed gradual clinical improvement. The discussion emphasized the importance of early detection of normocytic normochromic anemia in CKD patients because decreased erythropoietin production is a major factor. This study concluded that appropriate diagnosis and treatment of anemia due to CKD not only improve the clinical prognosis but also play a crucial role in preventing systemic complications and improving the patient's overall quality of life.